Comparative and correlational studies of the moisture, fat, flavor, and texture of cheese-filled and all-meat hotdogs - Osano, Joenalyn Planto
Five brands of all-meat hotdog and three brands of cheese-filled hotdog were purchased from a local supermarket to determine and compare their physico-chemical and sensory attributes (fat, moisture, texture and flavor.